Steering the ester and gamma-valerolactone selectivities in levulinic acid hydrogenation - Kasar, Gayatri B.; Date, Nandan S.; Bhosale, P. N.; Rode, Chandrashekhar V. (Energy Fuels, 2018)
Both alkyl esters and γ-valerolactone (GVL) derived from levulinic acid (LA) have applications as renewable transportation fuel/fuel additives. Non-noble metal cobalt supported on La2O3 catalyst was developed for efficient cascade LA hydrogenation to GVL via esterification. LA hydrogenation in methanol alone yielded methyl levulinate (MeLA) as a major product along with 43% of GVL. Interestingly, hydrogenation in water gave almost complete selectivity to GVL; nevertheless, it was associated with significant metal leaching. Suppression of metal leaching and enhancement in selectivity to GVL could be achieved by a methanol/water (95:5) solvent system. XRD analysis of La2O3-supported catalysts evidenced the characteristic peaks of a mixture of La2O3 and La(OH)3 phases. Basicity, as well as acidity, of the catalyst as determined by CO2 and NH3 TPD was due to these La2O3, Co–La, and La(OH)3 phases which played an important role in directing the product selectivity in levulinic acid hydrogenation. At the low temperature of 160 °C, almost equal selectivities of MeLA (47%) and GVL (43%) were observed, while higher temperature (200 °C) favored further hydrogenation of MeLA to GVL (75%). Similarly, with an increase in reaction time to 9 h, the GVL selectivity achieved was as high as 80%. The selectivity to MeLA and GVL in LA hydrogenation over Co/La2O3 catalyst can be altered by suitably adjusting the reaction conditions.